2019
DOI: 10.3390/en12050812
|View full text |Cite
|
Sign up to set email alerts
|

Embedded Discrete Fracture Modeling as a Method to Upscale Permeability for Fractured Reservoirs

Abstract: Fractured reservoirs are distributed widely over the world, and describing fluid flow in fractures is an important and challenging topic in research. Discrete fracture modeling (DFM) and equivalent continuum modeling are two principal methods used to model fluid flow through fractured rocks. In this paper, a novel method, embedded discrete fracture modeling (EDFM), is developed to compute equivalent permeability in fractured reservoirs. This paper begins with an introduction on EDFM. Then, the paper describes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…This fluid velocity increase inside the natural fractures (Figure 2(d)) is the primary reason for preferential flow paths and flow channeling due to fracture networks [49][50][51][52]. Multiple tracer transport studies on core samples of different length scales have shown that flow inside a fractured reser-voir is highly heterogeneous [52][53][54][55]. Natural fractures may also result in fracture/well communication; thus, they need to be adequately accounted for while designing the infill wells and hydraulic fractures [1,2].…”
Section: Determination Of Permeability Contrast With Matrix Andmentioning
confidence: 99%
See 1 more Smart Citation
“…This fluid velocity increase inside the natural fractures (Figure 2(d)) is the primary reason for preferential flow paths and flow channeling due to fracture networks [49][50][51][52]. Multiple tracer transport studies on core samples of different length scales have shown that flow inside a fractured reser-voir is highly heterogeneous [52][53][54][55]. Natural fractures may also result in fracture/well communication; thus, they need to be adequately accounted for while designing the infill wells and hydraulic fractures [1,2].…”
Section: Determination Of Permeability Contrast With Matrix Andmentioning
confidence: 99%
“…Thus, EDFM does not require a conforming mesh for the discrete fractures, which reduces the gridding complexity. Several authors have recently presented EDFM as a promising alternative to DFN and other upscaled single/multicontinuum models [25,52,53].…”
Section: Scaling Natural Fracture Strength To Permeability Usingmentioning
confidence: 99%
“…We will consider two solutions of incompressible (both solid skeleton and fluid) single phase flow problems. Note here we must deal with fissures explicitly either through DFM combined with local grid refinement (LGR) [26,58,60] or EDFM [39], but the good thing is that we just need to solve a single PDE, i.e., ∇ • q = 0. Both solutions will use linear pressure gradient boundary conditions [40].…”
Section: Computing Equivalent Permeability Kmentioning
confidence: 99%
“…In recent years, the EDFM is very popular due to its high compatibility with existing reservoir simulators (Yu et al, 2018;Dong et al, 2019;Zhang et al, 2020;Zhu et al, 2020). This method can smoothly embed fractures in the reservoir without impacting the existing grid.…”
Section: Introductionmentioning
confidence: 99%